Aesthetico-Cultural Cosmopolitanism and French Youth The Taste of the World - Cicchelli, Vincenzo (Consumption and Public Life, 2018)
By examining cultural consumption, tastes and imaginaries as a means of relating to the world, this book describes the effects of globalization on young people from an aesthetic and cultural perspective. It employs the concept of aesthetic-cultural cosmopolitanism to analyse the emergence of an aesthetic openness to alterity as a new generational 'good taste'. Aesthetico-Cultural Cosmopolitanism and French Youth critically examines the consumption of cultural products and imaginaries that provides genuine insight into social change, particularly in regard to young people who play the largest role in cultural circulation. This book will be of interest to a wide range of readers, including cultural theorists and students engaged in debates on cultural consumption, the globalization of culture and transnational aesthetic codes.